A case study on functionality and aesthetics of the St. James the great multipurpose hall interiors - Manuel, Maria Josefina Cecilia V.
The focus of the case study was on the improvement of the St. James the Great Parish Multipurpose Hall in Ayala Alabang Village in terms of functionality as well as aesthetics. Specifically, this study looked into the following design problems of the Multipurpose Hall (MPH): 1) the physical appearance of the place; 2) flexibility of the function of the place; and 3) sound insulation applied in the place. Using purposive sampling, 31 members from the St. James Renewal Movement have been selected as respondents of the survey and interview. Through site visits, observation checklist, surveys and interviews, information on the users' preferences for the design features of the MPH, as well as feasible solution to the problems identified were obtained. Results showed that most of the respondents were found to be complacent with how the MPH has been designed, while others, mostly the Youth and Singles members expressed their interest for changes to be made in the MPH interior design. The findings inferred that age has bearing on the respondents' perceptions as well as preferences; and the gender of the respondents has an influence on the colors that they have suggested for the improvements of the interior design of the MPH. They prefer beige or white walls and ceilings; dark brown or dark blue floors; and both white and yellow lights. Upon consolidation of data gathered, some solution for an improved MPH are recommended as follows: 1) installation of acoustic boards on the walls and ceilings for better sound absorption; 2) introduction of a better color scheme, lighting fixtures and material finishes that will make the MPH more aesthetically pleasing, and flexible in terms of the functionality of the place; and 3) repairing and/or replacing the existing doors with those that will not make noise when opened or closed.